Lactobacillus salivarius fermentation reduced glucosinolate and fibre in canola meal - Aljuobori, Ahmed; Abdullah, Norhani; Idrus, Zulkifli; Farjam, Abdoreza Soleimani; Liang, Juan Boo; Oskoueian, Ehsan (Canadian Center of Science and Education, 2014)
Local traditional fermented foods consisting of seven samples of tempoyak (made from fresh durian fruit), six samples of budu (made from boiled fish), four samples of tempeh (made from boiled soybean), two samples of vegetable pickle (made from raw cabbage) and one sample of tapai (made from cooked glutinous rice), were used as samples for the isolation of lactic acid bacteria (LAB). A number of samples for different fermented foods like tempoyak, budu and vegetable pickle were screened as they were fermented by microorganisms naturally present in the food. One hundred isolates were obtained and by sequential screening for catalase activity and Gram-staining, 20 isolates were determined to be Lactobacillus. Ten isolates with the highest enzymatic activities were selected based on the biochemical reactions of the API ZYM kit. Canola meal (CM) was treated with the ten Lactobacillus isolates in solid state fermentation for 30 days. The most efficient LAB isolate was identified as lactobacillus salivarius and significantly reduced the total glucosinolate and crude fibre content of CM by 38% and 16%, respectively.